Mapping Scientific Articles Published in the Journal of Translation Researches in the Arabic Language And Literature (2011-2019) - Saeideh Mirhaghjoo Langeroudi; Fatemeh Alinezhad Chamazkoti (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2020)
Throughout the past decades, the study and making scientific maps has been taken into consideration and raised as one of the scientific studies’ indicators in various fields. The present study examines scientific productions in the Journal of Translation Researches in the Arabic Language and Literature which is present at ISC. The purpose of this study is to review the authors' scientific activities in the Journal of Translation Researches in the Arabic Language and Literature, along with their scientific network in order to make their scientific information visible. This has been possible and tractable through the interactions between authors and Universities. This research is a scientometric study that was performed with a quantitative method and citation analysis. The research population contains all articles in the Journal of Translation Researches in the Arabic Language and Literature selected from 2011 to 2019, which are indexed in ISC science citation index (SCI). The maps were made using co-citation analysis and completed by VOSviewer software. The findings show that the authors’ scientific contributions in this journal are at a desirable level. On the other hand, there is a positive and significant correlation between the variables of scientific communication and scientific production. In other words, those authors with more productions are more involved with other authors in writing articles. The results of the present study emphasize on the importance of publishing articles in the Journal of Translation Researches in the Arabic Language and Literature and the scientific collaboration between authors and universities.